Daily high doses of atorvastatin alter neuronal morphology in a juvenile songbird model - Shuk C. Tsoi; Alicia C. Barrientos; David S. Vicario; Mimi L. Phan; Carolyn L. Pytte (PLoS ONE, 2025)
Statins are highly effective and widely prescribed cholesterol lowering drugs. However, statins cross the blood-brain barrier and decrease neural cholesterol in animal models, raising concern that long-term statin use may impact cholesterol-dependent structures and functions in the brain. Cholesterol is a fundamental component of cell membranes and experimentally decreasing membrane cholesterol has been shown to alter cell morphology in vitro. In addition, brain regions that undergo adult neurogenesis rely on local brain cholesterol for the manufacture of new neuronal membranes. Thus neurogenesis may be particularly vulnerable to long-term statin use. Here we asked whether oral statin treatment impacts neurogenesis in juveniles, either by decreasing numbers of new cells formed or altering the structure of new neurons. The use of statins in children and adolescents has received less attention than in older adults, with few studies on potential unintended effects in young brains. We examined neurons in the juvenile zebra finch songbird in telencephalic regions that function in song perception and memory (caudomedial nidopallium, NCM) and song production (HVC). Birds received either 40 mg/kg of atorvastatin in water or water vehicle once daily for 2–3 months until they reached adulthood. We labeled newborn cells using systemic injections of bromodeoxyuridine (BrdU) and quantified cells double-labeled with antibodies for BrdU and the neuron-specific protein Hu 30–32 days post mitosis. We also quantified a younger cohort of new neurons in the same birds using antibody to the neuronal protein doublecortin (DCX). We then compared numbers of new neurons and soma morphology of BrdU + /Hu+ neurons between statin-treated and control birds. We did not find an effect of statins on the density of newly formed neurons in either brain region, suggesting that statin treatment did not impact neurogenesis or young neuron survival in our paradigm. However, we found that neuronal soma morphology differed significantly between statin-treated and control birds. Somata of BrdU + /Hu+ (30–32 day old) neurons were flatter and had more furrowed contours in statin-treated birds relative to controls. In a larger, heterogeneous cohort of non-birthdated BrdU-/Hu+ neurons, largely born prior to statin treatment, somata were smaller in statin-treated birds than in controls. Our findings indicate that atorvastatin may affect neural cytoarchitecture in both newly formed and mature neurons, perhaps as a consequence of decreased cholesterol availability in the brain.